Influence of waste management on the construction management plan: a case study in Teresina - PI (Research, Society and Development, 2022)
The construction industry in Teresina is constantly growing, as a result of which a large amount of raw material from the environment is being consumed, as well as large quantities of waste being generated.The generation of waste from construction causes great concern, as it is still presented as one of the great generators of environmental impacts, and when poorly executed, its management can directly affect the performance of the contruction works.The objective of this work is to analyze the waste management system of a work, where, through a survey of the management practices carried out, identify the problems and generating sources, and then propose the necessary actions to improve its efficiency.For this analysis, a structured checklist was used with the phases of management at the construction site, with the purpose of gathering information that shows the not adequate or absence of these practices in the work studied.The results obtained demonstrate that the lack of inspection and awareness of the companies, directly affect the work plan, due to the fact that many actions are still necessary for an adequate waste management.Thus, with the implementation of an efficient management system, there will be an increase in the work organization, cost reduction, and a reduction in the environmental impact caused at construction sites.